Upaya Meningkatkan Keefektifan Bersihan Jalan Nafas Pada Pasien Penyakit Paru Obstruktif Kronik - Rizal Fauzi, Muhammad, Arief Wahyudi Jadmiko, S.Kep., Ns., M.Kep (2017)
Background:Chronic Obstructive Pulmonary Disease (COPD) has become the most common cause of death in Indonesia in which the prevalence increase each year. WHO estimated that by 2020 COPD will be in the third rank. This incidence increase due to air pollution such as smoke and caused by more people who has cigarettes smoking habit. Tobacco inside the cigarettes is the major cause of tissue damage and the onset of inflammation of the airways. In the long period, this can stimulate the excessive production of sputum which cause innefective airway. If it is not treated immediately, it will cause problems in the airway clearance. Objective:To give an overview of the efforts in improving the effectiveness of airway clearance in the patient with COPD at Methods:Method used was a descriptive method with a case study approach toward patient with Chronic Obstructive Pulmonary Disease (COPD) in the Hospital conducted from 12th until 14stof February, 2017 including five nursing processes start from assessment, determine diagnosis, intervention, implementation and evaluation. The data was obtained from the medical records, observations, interviews, physical examinations and supported journals concerning of COPD. Results:Patient indicated the patency/ looseness of the airway clereance, the secret has drop out after the treatment. Treatment due to chest physiotherapy and inhalation therapy of the airway clereance. Conclusion:The nursing problem of airway clearance has been done. The nursing treatment of effective cough, chest physiotherapy and inhalation therapy before and after the intervention has effect the cleanliness of the airway clearance. Independent nursing treatment is recommended for the patient with COPD such as conducting a deep breath and effective cough. Keywords: COPD, airway, chest physiotherapy, effective cough, inhalation therapy